2013 IEEE International Conference on Multimedia and Expo Workshops (ICMEW) 2013
DOI: 10.1109/icmew.2013.6618331
|View full text |Cite
|
Sign up to set email alerts
|

Towards semantic and affective content-based video recommendation

Abstract: Content-based recommendation is a popular framework for video recommendation, where the videos recommended are selected according to content similarity. Aiming at providing semantically similar videos to those already viewed by the user, most existing methods measure video similarity from tags or semantics-oriented features of videos. However, effec tive recommendations can also be based on affective content, which might be more significantly correlated to users' tastes and moods. We propose to combine semanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This is confirmed that the content is relevant to the user's interests. Yoshida et al [9] proposed collecting tags and visual and audio features from videos and mixes the semantic and effective information gathered to suggest videos to the user. The tag-based similarity is determined by counting the number of specific tags exchanged between the two different videos.…”
Section: Content-based Detection Reviewmentioning
confidence: 99%
“…This is confirmed that the content is relevant to the user's interests. Yoshida et al [9] proposed collecting tags and visual and audio features from videos and mixes the semantic and effective information gathered to suggest videos to the user. The tag-based similarity is determined by counting the number of specific tags exchanged between the two different videos.…”
Section: Content-based Detection Reviewmentioning
confidence: 99%